The Effect of Mutation and Promotion on Employee Performance With Job Satisfaction as An Intervening Variable at PT. Wahana Ottomitra Multiartha Tbk - Trisna Magdalena; Sofiyan Sofiyan; Cut Fitri Rostina; Yusuf Ronny Edward (CV. Aksara Global Akademia, 2024)
This study aims to see how employee performance in encouraging companies to set targets and see what things affect the level of employee performance. The data collection method is done through a questionnaire using a Likert scale. The sample taken was 112 people. Data processed using SmartPLS 3.0, analyzed by multiple regression. The results of this study state that Mutation has a positive and significant effect on Job Satisfaction at PT Wahana Ottomitra Multiartha Tbk 0.000 (<0.5) with a T-statistic of 3.624 (>1.96). The Original Sample value is positive, which is 0.362. Job promotion has a positive and significant effect on Job Satisfaction at PT Wahana Ottomitra Multiartha Tbk 0.000 (<0.5) with a T-statistic of 4.613 (>1.96). The Original Sample value is positive, which is 0.467. Mutation has a positive and significant effect on employee performance at PT Wahana Ottomitra Multiartha Tbk 0.009 (<0.5) with a T-statistic of 2.640 (>1.96). The Original Sample value is positive, which is 0.262. Job promotion has a positive and significant effect on employee performance at PT Wahana Ottomitra Multiartha Tbk 0.001 (<0.5) with a T-statistic of 3.426 (>1.96). The Original Sample value is positive, which is 0.358. Job satisfaction has a positive and significant effect on employee performance at PT Wahana Ottomitra Multiartha Tbk 0.010 (<0.5) with a T-statistic of 2.586 (>1.96). The Original Sample value is positive, which is 0.269. Job Satisfaction can mediate the effect of mutation on employee performance at PT Wahana Ottomitra Multiartha Tbk with a significant 0.044 (<0.5) with a T-statistic of 2.018 (>1.96). The Original Sample value is positive, which is 0.098. Job Satisfaction can mediate the effect of job promotion on employee performance at PT Wahana Ottomitra Multiartha Tbk with a significant 0.025 (<0.5) with a T-statistic of 2.252 (>1.96). The Original Sample value is positive, which is 0.126. It is known that the R Square value for each construct, namely Job Satisfaction, is 0.614 with an Adjusted R Square of 0.607, which means 60.7%. So mutations and promotions have a contribution in explaining the job satisfaction variable. Based on the results on employee performance, there is an R Square of 0.664 with an Adjusted R Square of 0.654, which means 65.4%. So mutations and promotions have a contribution in explaining the employee performance variable.